Efficacy and safety of using premedication with simethicone/Pronase during upper gastrointestinal endoscopy examination with sedation: A single center, prospective, single blinded, randomized controlled trial. Issue 1 (12th October 2017) - Zhang, Ling‐Ye; Li, Wen‐Yan; Ji, Ming; Liu, Fu‐Kun; Chen, Guang‐Yong; Wu, Shan‐Shan; Hao, Qian; Zhai, Hui‐Hong; Zhang, Shu‐Tian
Abstract : Background and Aim: To investigate the efficacy and safety of premedication with simethicone/Pronase during esophagogastroduodenoscopy (EGD) with sedation. Methods: Six hundred and ten patients were randomly allocated to two groups based on type of premedication given. Premedication used in the control group was 10 mL lidocaine hydrochloride mucilage (LHM, N = 314) and premedication used in the intervention group was 80 mL simethicone/Pronase solution plus 10 mL lidocaine hydrochloride mucilage (SP/LHM, N = 296). EGD was done under sedation. Visibility scores, number of mucosal areas that needed cleansing, water consumption for cleansing, time taken for examination, diminutive lesions, pathological diagnosis, patients' gag reflex and oxygenation (pulse oximetry) were recorded. Results: SP/LHM has significantly lower total visibility score than LHM (7.978 ± 1.526 vs 6.348 ± 1.097, P < 0.01). During the procedure, number of intragastric areas that needed cleansing and amount of water consumed were significantly less in the SP/LHM than in the LHM group ( P < 0.01). In SP/LHM ( P = 0.01), endoscopy procedure duration was significantly longer. Although there was no significant difference in rate of detection of diminutive lesions between LHM and SP/LHM, the endoscopist carried out more biopsies in SP/LHM. This led to a higher rate of diagnosis of atrophic gastritis ( P = 0.014) and intestinal metaplasia ( P = 0.024). There was no significant difference in gag reflex ( P = 0.604) and oxygenation during the endoscopy procedure for either group of patients. Conclusion: Routine use of premedication with simethicone/Pronase should be recommended during EGD with sedation.